Cadexomer iodine effectively reduces bacterial biofilm in porcine wounds ex vivo and in vivo. Issue 3 (13th March 2019) - Roche, Eric D.; Woodmansey, Emma J.; Yang, Qingping; Gibson, Daniel J.; Zhang, Hongen; Schultz, Gregory S.
Abstract : Biofilms are prevalent in non‐healing chronic wounds and implicated in delayed healing. Tolerance to antimicrobial treatments and the host's immune system leave clinicians with limited interventions against biofilm populations. It is therefore essential that effective treatments be rigorously tested and demonstrate an impact on biofilm across multiple experimental models to guide clinical investigations and protocols. Cadexomer iodine has previously been shown to be effective against biofilm in various in vitro models, against methicillin‐resistant Staphylococcus aureus biofilm in mouse wounds, and clinically in diabetic foot ulcers complicated by biofilm. Similarities between porcine and human skin make the pig a favoured model for cutaneous wound studies. Two antiseptic dressings and a gauze control were assessed against mature biofilm grown on ex vivo pig skin and in a pig wound model. Significant reductions in biofilm were observed following treatment with cadexomer iodine across both biofilm models. In contrast, silver carboxymethylcellulose dressings had minimal impact on biofilm in the models, with similar results to the control in the ex vivo model. Microscopy and histopathology indicate that the depth of organisms in wound tissue may impact treatment effectiveness. Further work on the promising biofilm efficacy of cadexomer iodine is needed to determine optimal treatment durations against biofilm.